Ahmad Dahlan's Educational Legacy: Answering Education Challenges in Era 4.0 - Hamzah, Amir; Abu Bakar, M. Yunus (Sumber Belajar Sejahtera, 2025)
This research aims to find out how K.H Ahmad Dahlan's views on Islamic education and its relevance to modern Islamic education. The method used in this research is library research using a descriptive qualitative approach. In the research, the researcher attempts to collect data through several books, articles, journals, or other sources related to K.H. Ahmad Dahlan's Islamic education thought, then the researcher analyses it and explores significantly related to the relevance of Ibn Khaldun's Islamic education. The result of this research is that KH Ahmad Dahlan pioneered the renewal of Islamic education in Indonesia by integrating religious and general sciences to produce a generation of Muslims who are knowledgeable and noble. He used dialogical learning methods that involved hands-on practice, and adopted a modern education system in the management of the institution. His progressive thinking remains relevant, making Islamic education under Muhammadiyah an innovative and future-orientated education model.